Persepsi, Pemahaman dan Tingkat Penerapan Sistem Pertanian Organik oleh Petani dalam Budidaya Padi Sawah di Sumatera Barat - Rifda Roswita; Eva Riza (Jurnal Pembangunan Nagari, 2019)
The Government of West Sumatra has gradually encouraged the development of organic agriculture, both before and after the organic village program was launched by the Ministry of Agriculture. This study aims to determine: (1) farmers 'perceptions of organic farming systems, (2) farmers' understanding of organic farming systems (3) and the level of application of organic farming systems. The assessment was carried out in March - July 2017 in 3 (three) districts in West Sumatra, namely districts that implemented organic village programs in 2016 and which developed organics through programs before 2016. In each district, one executive group of farmers was selected as an event organic village program in 2016 (in this study it is referred to as a new organic village) and one farmer group that implements organic programs before 2016 (in this study it is referred to as an old organic village). Selected districts are Padang Pariaman, Solok and Limapuluh Kota Regencies. Sampling is done by purposive sampling system. Primary data collection is done by Focus Group Discussion and individual interviews. The data collected are farmers' internal characteristics, farmers' perceptions of organic farming, farmers' understanding of organic farming systems, and the level of application of farmers to organic farming systems. Data were analyzed descriptively and statistically by testing the paired samples T-Test and Mann Whitney difference test to compare between farmers implementing organic village programs and non organic village programs. The results showed that (1) farmers 'perceptions of the nature of the innovation of the organic farming system as a whole, approached a score of 4, namely lower costs, higher production, more profitable, according to farmers' needs, easy to implement, easy to try, and easily observed results. (2) farmers' understanding of the overall components of the organic farming system is high, with a value of 78.55. While the 5 highest understanding variables of farmers are harvest and post-harvest handling and land management and land fertility. The understanding of farmers that still needs to be improved is the understanding of farmers on the conversion period, where some farmers are not very aware of the objectives, and the duration of land conversion even though it has been implemented, (3) the level of application of organic farming system components to organic village farmers is lower (73, 93%) than old organic village farmers (93.21%).